Rosmarinic acid prevents fibrillization and diminishes vibrational modes associated to β sheet in tau protein linked to Alzheimer's disease. (1st January 2017) - Cornejo, Alberto; Aguilar Sandoval, Felipe; Caballero, Leonardo; Machuca, Luis; Muñoz, Patricio; Caballero, Julio; Perry, George; Ardiles, Alejandro; Areche, Carlos; Melo, Francisco
Abstract: Alzheimer's disease is a common tauopathy where fibril formation and aggregates are the hallmark of the disease. Efforts targeting amyloid-β plaques have succeeded to remove plaques but failed in clinical trials to improve cognition; thus, the current therapeutic strategy is at preventing tau aggregation. Here, we demonstrated that four phenolic diterpenoids and rosmarinic acid inhibit fibrillization. Since, rosmarinic acid was the most active compound, we observe morphological changes in atomic force microscopy images after treatment. Hence, rosmarinic acid leads to a decrease in amide regions I and III, indicating that rosmarinic acid prevents β-sheet assembly. Molecular docking study inside the steric zipper model of the hexapeptide 306 VQIVYK 311 involved in fibrillization and β sheet formation, suggests that rosmarinic acid binds to the steric zipper with similar chemical interactions with respect to those observed for orange G, a known pharmacofore for amyloid.